2004
DOI: 10.1016/j.physleta.2004.03.074
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of giant electron–gamma bursts generated by extensive atmospheric showers in thunderclouds

Abstract: The existence of a new phenomenagiant electron-gamma bursts is established. The bursts are generated in thunderclouds as a result of the combined action of runaway breakdown and extensive atmosphere showers (RB-EAS). The experiments were fulfilled at the Tien Shan Mountain Scientific Station using EAS-Radio installation. This specially constructed installation consists of a wide spread EAS trigger array and a high time resolution radiointerferometer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…TGF spectra measured by RHESSI reveal energies up to 30 MeV , in agreement with energies predicted by the runaway relativistic electron breakdown mechanism triggered by cosmic rays (Roussel-Dupré and Gurevich 1996;Gurevich et al 2004;Roussel-Dupré et al 2005), while most of TLE structures are explained by conventional processes (Pasko 2006). Most recent developments show that for fast (< a few ms), high current (>100 kA) positive lightning, the high altitude discharge is dominated by a diffusive air glow driven by conventional breakdown and producing TLEs at high altitudes (>60-70 km), followed by runaway breakdown, at the origin of TGFs, that initiates at the top of the cloud (∼15 km) and develop upwards to altitudes exceeding 90 km.…”
Section: Tles and Tgfs Generation Mechanismssupporting
confidence: 77%
See 1 more Smart Citation
“…TGF spectra measured by RHESSI reveal energies up to 30 MeV , in agreement with energies predicted by the runaway relativistic electron breakdown mechanism triggered by cosmic rays (Roussel-Dupré and Gurevich 1996;Gurevich et al 2004;Roussel-Dupré et al 2005), while most of TLE structures are explained by conventional processes (Pasko 2006). Most recent developments show that for fast (< a few ms), high current (>100 kA) positive lightning, the high altitude discharge is dominated by a diffusive air glow driven by conventional breakdown and producing TLEs at high altitudes (>60-70 km), followed by runaway breakdown, at the origin of TGFs, that initiates at the top of the cloud (∼15 km) and develop upwards to altitudes exceeding 90 km.…”
Section: Tles and Tgfs Generation Mechanismssupporting
confidence: 77%
“…Furthermore, the source of these phenomena must by all indications stem from a fundamentally new physical process that could have much broader implications and manifestations throughout the universe. Radio frequency emissions from lightning activity observed in the environment of other planets could be the signature of a physical process (runaway breakdown) proposed by several authors (Roussel-Dupré and Gurevich 1996;Gurevich et al 2004;Roussel-Dupré et al 2005) for the Earth environment (Zarka et al 2004). Such processes could be much more efficient on Jupiter (Dwyer et al 2006).…”
Section: Introductionmentioning
confidence: 92%
“…Their source can be explained by runaway electron avalanches within electrified clouds, triggered by the background population of cosmic ray secondary (Tierney et al, 2005). Gurevich and Zybin (2005) and Gurevich et al (2004) showed that extensive air showers triggered by energetic cosmic rays can also seed runaway breakdown processes that produce narrow bipolar pulses and TGFs with weak light emission. Williams et al (2006) shows that the RHESSI TGF altitude source in the upper troposphere/lower stratosphere can explain that TGFs are more frequent in low-latitude regions were the tropopause height is higher (Williams et al, 2006).…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…However, the Cherenkov emission mechanism is more efficient in denser media than air, like water and ice. Additionally, radio emission in air showers was claimed to be dependent on the geoelectric field, and it was found that strong electric fields in thunderstorm clouds can amplify the measured radio amplitudes (Mandolesi et al 1974;Gurevich et al 2004;Buitink et al 2007). …”
Section: Introductionmentioning
confidence: 99%